Environmental histories of the Cold War - McNeill, John Robert; Unger, Corinna R. (Publications of the German Historical Institute., 2010)
Environmental Histories of the Cold War explores the links between the Cold War and the global environment, ranging from the environmental impacts of nuclear weapons to the political repercussions of environmentalism. Environmental change accelerated sharply during the Cold War years, and so did environmentalism as both a popular movement and a scientific preoccupation. Most Cold War history entirely overlooks this rise of environmentalism and the crescendo of environmental change. These historical subjects were not only simultaneous but also linked together in ways both straightforward and surprising. The contributors to this book present these connected issues as a global phenomenon, with chapters concerning China, the USSR, Europe, North America, Oceania, and elsewhere. The role of experts as agents and advocates of using the environment as a weapon in the Cold War or, contrastingly, of preventing environmental damage resulting from Cold War politics is also given broad attention.